THE USE OF ANIMATION MEDIA FOR SCIENCE LEARNING IN GROUP B CHILDREN AT RA CAHAYA INSANI - Afsoh, Irza Pradita; Akhtim Wahyuni (Antis Publisher, 2024)
Objective: This study aims to describe the application of animation media in science learning and evaluate its effects on the understanding and interest of group B children at RA Cahaya Insani. The focus is on how animation media facilitates comprehension and fosters enthusiasm for learning abstract concepts. Methods: A qualitative descriptive approach was employed, utilizing observations, interviews, and documentation as data collection techniques. This method allowed for an in-depth exploration of the interactions between children, teachers, and the animation media. Results: The findings indicate that animation media significantly improves children's grasp of abstract concepts, such as the water cycle, by providing engaging and clear visualizations. Children exhibited increased enthusiasm and active participation in class activities. Teachers found that animation media eased the delivery of complex materials while encouraging critical thinking among students. Despite technical challenges like limited device availability, these were effectively addressed through meticulous planning and creative strategies by teachers. Novelty: This study highlights the innovative use of animation media in early childhood education, emphasizing its potential to enhance both cognitive and social development. It underscores the role of technology in creating effective and enjoyable science learning experiences, suggesting its broader application for diverse science topics in the future.